Caribbean Jewish crossings : literary history and creative practice - Casteel, Sarah Phillips, 1974-; Kaufman, Heidi, 1969- (New World studies., 2019)
"This books highlights the historical convergence of African and Jewish immigrants to the Caribbean Islands by comparing their literatures of oppression, migration, and survival"--